2005
DOI: 10.1002/ffj.1696
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between flavour compounds andβ-lactoglobulin: approach by NMR and 2D/3D-QSAR studies of ligands

Abstract: Interactions between flavour compounds and β-lactoglobulin (BLG) have been the subject of several studies, but there are no unanimous binding site explanations. In our laboratory, interactions between BLG, and two flavour compounds, β-ionone and γ-decalactone, were studied by 2D-NMR spectroscopy. It appears that several amino acids affected by binding of γ-decalactone are buried in the central cavity, whereas binding of β-ionone affects amino acids located in a groove near the outer surface of the protein. 2D/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Some of the common methods used to study binding of flavor compounds to proteins have included headspace gas chromatography (Franzen and Kinsella 1974; Kinsella 1989; Philippe and others 2003; Heng and others 2004), NMR (Jung and others 2002; Lubke and others 2002; Tromelin and Guichard 2006), fluorescence (Damodaran and Kinsella 1980; Dufour and Haertle 1990; Relkin and others 2001), equilibrium dialysis (Beyeler and Solms 1974; Druaux and others 1995; Fares and others 1998), and liquid chromatography (Pelletier and others 1998; Andriot and others 1999; Jouenne and Crouzet 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the common methods used to study binding of flavor compounds to proteins have included headspace gas chromatography (Franzen and Kinsella 1974; Kinsella 1989; Philippe and others 2003; Heng and others 2004), NMR (Jung and others 2002; Lubke and others 2002; Tromelin and Guichard 2006), fluorescence (Damodaran and Kinsella 1980; Dufour and Haertle 1990; Relkin and others 2001), equilibrium dialysis (Beyeler and Solms 1974; Druaux and others 1995; Fares and others 1998), and liquid chromatography (Pelletier and others 1998; Andriot and others 1999; Jouenne and Crouzet 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The binding of flavor compounds to a number of specific proteins has been investigated. The protein most studied in this context is beta‐lactoglobulin (Andriot and others 2000; Guichard 2000; Jouenne and Crouzet 2000; Reiners and others 2000; Seuvre and others 2002; Tromelin and Guichard 2006). Bovine serum albumin (BSA) and casein have also received considerable attention (Damodaran and Kinsella 1980; Chobpattana and others 2002; Guichard 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of protein-containing matrices, next to dry matter and overall protein content, the pH in water, the particle size in solution, the DWPD, the overall ash content, and the process history of the mostly powdered, raw material should be specified. Only if the matrix constituents are better specified can highly elaborated quantitative structure–property relationships (QSPRs), as presented by Tromelin et al for polysaccharide matrices and Tromelin and Guichard for β-lactoglobulin, unfold their potential in more practical applications. In order to increase the reliability of K MG value forecasts, a sufficiently variable data pool is necessary, but so far does not exist for the majority of the analyzed aroma compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Although Davis and Dubos (1947) noted that βLg bound about half as much oleic acid as serum albumin, it was Groves et al (1951) who showed that 2 mol/mol of sodium dodecyl sulfate not only bound but had a stabilizing effect on thermal denaturation. Since then, a large number of ligands for βLg has been identified and that number is still increasing ( Sawyer, 2003 ; Tromelin and Guichard, 2006 ; Cherrier et al, 2013 ; Le Maux et al, 2014 ; Loch et al, 2015 , 2018 ). To date, the only definitive ligand binding site is within the central calyx despite there being several experimental studies indicating that alternative sites may exist ( Frapin et al, 1993 ; Dufour et al, 1994 ; Lange et al, 1998 ; Narayan and Berliner, 1998 ; Lübke et al, 2002 ; Yang et al, 2008 , 2009 ; Edwards and Jameson, 2020 ).…”
Section: β-Lactoglobulinmentioning
confidence: 99%